Vibration analysis of a beam structure attached with two dynamic vibration absorbers - Jaini, Norhaslina (2014)
A fixed end beam is a structural element supported at both sides which carries load primarily in flexure that may experience vibration as it does carry vertical loads and gravitational forces. Its exposure to vibration can lead to excessive deflections and failure of to the structure. The aim of this research is to develop the application of dynamic vibration absorber on a fixed end beam structure. A classical mathematical model based on dynamic vibration absorber theory is improved by an analytical derivation until two degree of freedoms. The theoretical model is verified by experimental works. In experimental, two vibration absorbers was fabricated to be installed to the beam in four different conditions; and subjected to a force vibration frequency loading using an exciter. The resonance frequencies of interest were 11.23Hz and 35.45Hz. The vibration level that occurred on the beam is measured by comparing the effect of absorber presence to see the reduction in its amplitudes. Based on the experimental and theoretical analysis, both shows reduction in the beam amplitudes. From those results can be concluded that the dynamic vibration absorber has an ability to reduce and suppresses the beam vibration whereas the third condition has been chosen as the best arrangement where the persistent reduction results recorded 95 and 99 percents reduction of first and second DVA respectively. The knowledge gained from this research can be used to minimize the vibration amplitude of a structures and machines, increasing their life-span simultaneously. The other benefit comes from this research in specific or potential application aspect is it could control vibration in building or bridge structure and airplane wing flutter control.